Answer: p = 6 Step-by-step explanation: Simplifying 4p = 6p + -12 Reorder the terms: 4p = -12 + 6p Solving 4p = -12 + 6p Solving for variable ‘p’. Move all terms containing p to the left, all other terms to the right. Add ‘-6p’ to each side of the equation. 4p + -6p = -12 + 6p + -6p Combine like terms: 4p + -6p = -2p -2p = -12 + 6p + -6p Combine like terms: 6p + -6p = 0 -2p = -12 + 0 -2p = -12 Divide each side by ‘-2’. p = 6 Simplifying p = 6 Log in to Reply

Answer:-2p+18

Step-by-step explanation:Combine like terms

Answer:p = 6

Step-by-step explanation:Simplifying

4p = 6p + -12

Reorder the terms:

4p = -12 + 6p

Solving

4p = -12 + 6p

Solving for variable ‘p’.

Move all terms containing p to the left, all other terms to the right.

Add ‘-6p’ to each side of the equation.

4p + -6p = -12 + 6p + -6p

Combine like terms: 4p + -6p = -2p

-2p = -12 + 6p + -6p

Combine like terms: 6p + -6p = 0

-2p = -12 + 0

-2p = -12

Divide each side by ‘-2’.

p = 6

Simplifying

p = 6